Studi Timbulan, Komposisi, Karakteristik dan Potensi Daur Ulang Sampah Stasiun Kereta Api di Kota Padang - Yurizka Trialisa; Rizki Aziz; Yommi Dewilda (Jurnal Serambi Engineering, 2025)
The increase in the number of train stations in Padang City has an impact on the increase in the amount of waste generated, so it is necessary to know the amount of waste generated so that effective and efficient management can be carried out. This research aims to analyse the generation, composition, characteristics and recycling potential of waste in railway stations in Padang City and provide recommendations for appropriate waste management. The method in this research is based on SNI 19-3964-1994 on methods of collecting and measuring samples of urban waste generation and composition. The measurement results for the total waste generation at Padang City Railway Station were 316.08 kg/d or 0.316 tons/d. The composition of the station waste is 49.96% plastic waste, 20.42% food waste, 9.88% paper waste, 6.65% wood and garden waste, 0.63% metal/can waste and 12.46% other waste. The physical characteristics are the specific weight of the waste of 0.06 Kg/L. Chemical characteristics include water content 16.19%, volatile content 73.73%, ash content 8.80%, fixed carbon content 1.27% and C/N ratio 23.14%. The biological properties of the biodegradability fraction test were 58.55%. The recycling potential for food waste is 94.91%, yard waste 100%, paper waste 47.66%, plastic waste 86.78% and can/metal waste 100%. Recommendations for waste management in this study include sorting waste by type and using different labels or colours for waste containers.